I'll watch your baby : a novel - Viel, Neena (St. Martin's Griffin, 2026)
"A suffocating and sharp narrative horror novel for fans of Victor LaValle and The Reformatory from "addictive" (Publishers Weekly) horror author Neena Viel, I'll Watch Your Baby is a haunting reimagining of Linda Taylor--known as the original Welfare Queen-pursued, scrutinized, celebrated and vilified, and the impact her image has had for generations. 1974. Lottie Turner is already infamous. Running a wheel of schemes and scams, she's willing to work for what she wants in...creative ways. But no business is more lucrative than desperate families looking to adopt a child-and there's only one way to procure children quickly. And the only way to take what's owed you is to cross the line no one else is willing to cross. 1994. Bless has finally found the family she deserved. After suffocating slowly with lackluster parents and a non-starter past, she's found the friends that means everything to her. That she'd live and die for. As they make their way across the country, one smash and grab at a time, Bless is used to acting fast and thinking on her feet. But someone is playing a long game. Someone has unfinished business. Soon Bless is trapped in a web of horrors past and present, where the only escape hatch is a path only she can walk, if she finds the courage to take it"--